95歳の超高齢者に発症した抜歯後深頸部膿瘍の1例 - 河原, 康; 渡邉, 裕之; 石井, 興; 宮地, 斉; 後藤, 満雄; 神谷, 祐司 (日本口腔外科学会雑誌, 2013)
A deep neck abscess is a serious condition that rapidly spreads by bacterial infection in facial planes and spaces of the neck, as well as in surrounding tissues. We report the case of a deep neck infection triggered by teeth extraction in a very elderly patient. A 95-year-old woman presented with severe neck pain and swelling that progressed rapidly over 3 days following teeth extraction at a local private dental clinic. Laboratory studies on the first visit showed acute inflammatory responses: the white-cell count was 35,200 /mm3, and the C-reactive protein level was 38.72 mg/dL. Contrast-enhanced computed tomographic images revealed that an abscess had spread widely into the neck and caused internal jugular vein obstruction. The patient therefore immediately, underwent surgical drainage through both neck and intraoral incisions under general anesthesia on the day of arrival. Airway management with intratracheal intubation was required for 5 days in the intensive care unit, with the administration of antibiotics. The patient was discharged from our hospital after complete recovery with no complications in 43 days. Prompt diagnosis and surgical drainage were key to successful treatment.